Influence of hypoxic conditions of lowlands and midlands of Ukraine on the functional state of young biathlonists aged 14–16 - Мулик, Вячеслав Володимирович (Slobozhanskyi Herald of Science and Sport, 2016)
Mulyk V. Purpose: to explore influence of lowlands and midlands on cardiovascular, respiratory and neuromuscular systems’ functioning of young biathlonists. Material & Methods: theoretical analysis and summarizing of scientifically-methodical literature, pedagogical supervisions, medicobiologic methods of functional state determination of young biathlonists. Results: affecting of hypoxic conditions of midlands on the functioning of cardiovascular, respiratory and neuromuscular systems’ of young biathlonists is ascertained. Conclusions: it is determined that the period of critical acclimatization to the mountain conditions for young biathlonists passes during 7–8 days provided correct construction of training process.